The Use of Instagrams as A Digital Communication Media by Holyspicy in The Covid-19 Pandemic - Tutiasri, Ririn Puspita; Widiastuti, Eunike Jayanti; Murti, Sesilia Tri Ria; Priscillia, Inggrid (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2021)
The growing business market in Indonesia, especially in the culinary sector, is currently getting benefits from the presence of social media. Social media is now an unforgettable tool for almost all entrepreneurs, especially for entrepreneurs in the culinary field to promote their products in the midst of the Covid-19 pandemic. Instagram provides various facilities for its users, especially in this case users who use Instagram to carry out product and brand promotion activities. Fast food is one of the culinary businesses that are currently booming, and Holyspicy is one of the culinary producers that uses Instagram as a medium of communication for promotion. This research focuses on how Instagram as a social media is used by Holyspicy as a main marketing and promotion tool. The research method used in this research is descriptive qualitative method. The theory used in this research is new media theory. Based on the results of the research, Instagram played an important role in Holyspicy's culinary business as a marketing and sales communication medium during the Covid-19 pandemic, as evidenced by the fact that during the Covid-19 pandemic, the income obtained by Holyspicy remained stable and actually experienced a significant increase at the beginning of the Covid-19 pandemic. Management of Instagram features such as hashtags, photo uploads, photo titles, and replying to customer comments also affects consumer buying interest.